PERAN APLIKASI RUANG GURU SEBAGAI MEDIA KOMUNIKASI ORANG TUA DAN ANAK DALAM MEMOTIVASI BELAJAR - Amalliah Amalliah (Yayasan Akrab Pekanbaru, 2019)
Tutoring becomes one of the even mandatory for students in dealing with subjects that are not easily schooled, the difficulties that are often faced by students the number of subjects and lack of creativity of teachers in explaining class is one option to seek tutoring outside of school, only time and costs become one the obstacles faced and also congestion added to the long school hours. The teacher room site is one alternative that provides ease of learning with easily and visually displayed material that can motivate students to learn and parents can also learn together and also monitor learning at home. By using learning motivation theory and the uses and gratifications theory where students have the desire and hope to achieve good grades and also find alternative ways of learning that are easy and interesting to understand, this encouragement is also what parents want to realize to motivate their children by enrolling children his children follow study hours outside school hours in the hope that their children can improve their achievement at school and can easily do their school assignments and learn together with their parents at home so that parents can continue to provide motivation to their children.